Alumina substrate for high frequency applications - Alias, Rosidah; Ibrahim, Azmi; Mohd Shapee, Sabrina; Yahya, Mohamed Razman; Awang Mat, Abd. Fatah; Hashim, Mansor (Universiti Putra Malaysia Press, 2005)
The rapidly growing wireless industry needs new high performance materials to build low loss, high density, thermally stable integrated packages. Ceramic is one of the materials that can be used for thick film technology in high frequency application due the excellent combination of electrical, thermal and mechanical properties. This paper discusses some properties of alumina substrate which suitable for microwave applications.